Ecopath modelling approach for the impact assessment of a small-scale coastal aquaculture system in Goa, India - Lekshmi, N. Manju; Sreekanth, G. B.; Singh, Narendra Pratap; Vennila, A.; Kumar, R. Ratheesh; Pandey, P K (Indian Journal of Fisheries, 2020)
In this study, the ecological impacts of introduction of cage aquaculture employing small cages integrating shellfish and finfish in coastal water bodies of Goa, situated in the west coast of India were analysed using Ecopath with Ecosim model. A multispecies cage aquaculture system incorporating Lutjanus argentimaculatus, Etroplus suratensis and Perna viridis was established in an estuarine ecosystem. The Ecopath model identified 12 functional groups starting from detritus (trophic level=1) to large benthic carnivores (trophic level=3.72). The ecosystem statistics such as total system throughput (8672 g m-2 year-1), gross efficiency (0.001), primary production/respiration (1.4), net system production (1028.2 g m-2 year-1) and system omnivory index (0.26) indicated that the ecosystem was highly productive and in a developing stage. With a medium rate of recycling (Finn’s Cycling Index=11.7%), high system throughput, high system overhead (79%) and moderate omnivory index (0.26), the food web was found to be immature having an organized trophic network with high production. Simulations of the various expanding scenarios for the cage culture within the ecosystem were explored using Ecosim. A scenario in which two cages each for pearlspot and red snapper and 20 mussel ropes was identified as a sustainable solution without sacrificing the threshold biomass for the functional groups of fish species [WU1] . The study provided useful insights and methodology towards assessing aquaculture in coastal ecosystems in terms of ecosystem structure and function.Keywords: Coastal cages, Ecopath with Ecosim model, Ecosystem impacts, Estuarine, Multispecies, Simulation [WU1]These are the ecological groups consists of fish species